Bimetallic Nanoparticles in Supported Ionic Liquid Phases as Multifunctional Catalysts for the Selective Hydrodeoxygenation of Aromatic Substrates. Issue 39 (3rd September 2018) - Offner‐Marko, Lisa; Bordet, Alexis; Moos, Gilles; Tricard, Simon; Rengshausen, Simon; Chaudret, Bruno; Luska, Kylie L.; Leitner, Walter
Abstract: Bimetallic iron–ruthenium nanoparticles embedded in an acidic supported ionic liquid phase (FeRu@SILP+IL‐SO3 H) act as multifunctional catalysts for the selective hydrodeoxygenation of carbonyl groups in aromatic substrates. The catalyst material is assembled systematically from molecular components to combine the acid and metal sites that allow hydrogenolysis of the C=O bonds without hydrogenation of the aromatic ring. The resulting materials possess high activity and stability for the catalytic hydrodeoxygenation of C=O groups to CH2 units in a variety of substituted aromatic ketones and, hence, provide an effective and benign alternative to traditional Clemmensen and Wolff–Kishner reductions, which require stoichiometric reagents. The molecular design of the FeRu@SILP+IL‐SO3 H materials opens a general approach to multifunctional catalytic systems (MM′@SILP+IL‐func). Abstract : A bimetallic, bifunctional catalyst composed of iron–ruthenium nanoparticles immobilized on an acid‐functionalized supported ionic liquid phase (FeRu@SILP+IL‐SO3 H) was developed. This catalyst showed high activity for the hydrodeoxygenation of aromatic ketones and excellent selectivity towards aromatic deoxygenation products.